"Blind" interviewing: Is ignorance bliss?. Issue 9 (20th October 2016) - Rivard, Jillian R.; Pena, Michelle M.; Schreiber Compo, Nadja
ABSTRACT: Current investigative interviewing guidelines [e.g., Technical Working Group: Eyewitness evidence. (1999). Eyewitness evidence: A guide for law enforcement . U.S. Department of Justice, Office of Justice Programs, National Institute of Justice. Retrieved fromhttps://www.ncjrs.gov/pdffiles1/nij/178240.pdf ] suggest that interviewers review available case information prior to conducting a witness interview. The present study investigated the effect of interviewers' pre-interview awareness of crime details on eyewitnesses' memory and interviewer behaviour shortly after a mock crime or a week later. Results indicate that blind interviewers with no knowledge about the crime elicited more correct information than those who were correctly informed about the crime. Differences in interviewer behaviour emerged only in the very first question of the interview: Blind interviewers were more likely to begin the interview with a non-suggestive question than the informed interviewers. Blind interviewers also recalled more details than the informed interviewers when asked to generate a report after the witness interview documenting the witness' account.